Behind the use of Code Switching and Code Mixing on Maudy Ayunda’s Youtube Video Content - Juliani Putri, Anita; Dwi Putri Maharani; Yesika Dian Saputri; Teguh Sarosa (International Journal of English and Applied Linguistics (IJEAL), 2025)
Bilingualism is a linguistic phenomenon characterized by the use of two languages in everyday life. In a bilingual context, communication practices often give rise to the phenomena of code switching and code mixing as language strategies. Code switching is understood as the practice of alternating between languages in discourse, while code mixing entails the incorporation of components from different languages into one utterance without an entire switch of language. A descriptive qualitative method was utilized in this study to analyze the observed phenomena. The research data was obtained from a video podcast by Maudy Ayunda and Jovial da Lopez entitled Dating Tips: 'Jangan Dikit-Dikit Putus". The data collection technique was carried out by watching and transcribing all the utterances in the video, then identifying and grouping the utterances that contained code switching and code mixing. Data analysis emphasized the process of identification, grouping, and interpretation of linguistic data. This study aims to investigate and understand the functions and roles of code switching and code mixing in conveying information, shaping audience perceptions, and representing the speaker's social identity. The results show that code mixing is more dominant than code switching, with alternation being the most common form. These findings indicate that the use of two languages plays a role in clarifying meaning, emphasizing messages, and creating a flexible and natural communication style in casual conversations on digital media.